(untitled) (Journal of Hama University, 2024)
This current research aimed to identify the obstacles to using the VARK model from the point of view of basic education teachers in Damascus city schools. Therefore, the descriptive analytical approach was followed, and a questionnaire was designed directed to basic education teachers in Damascus city schools, including (42) items distributed in three areas: obstacles related to the school environment, obstacles related to the educational process, and obstacles related to the teacher. The questionnaire was applied to a sample of (178) male and female teachers. The results of the research showed that the obstacles to using the VARK model, in the three areas of the questionnaire, are, in order: obstacles related to the teacher first, obstacles related to the educational process second, and obstacles related to the school environment third. The most significant obstacle to their use of the VARK model is overcrowding the classroom with large numbers of students. The statistical treatment also showed that there is no difference between the average scores of the teachers at the significance level (0.05) on the questionnaire of the obstacles to their use of the FARC model according to the academic qualification variable, and the absence of a statistically significant difference at the significance level of (0.05) between the average scores of the teachers in the research sample on the questionnaire of the obstacles according to For the variable of experience in teaching, there was no statistically significant difference at the significance level (0.05) between the average grades of the teachers in the research sample according to the academic grade variable.